PENGARUH LNGKUNGAN KERJA, BUDAYA ORGANISASI DAN MOTIVASI TERHADAP KINERJA KARYAWAN PADA PT. FAST FOOD INDONESIA, TBK (KFC INDONESIA) - Tantyo Setyowati; Ellen Artha (Jurnal Manajemen FE-UB, 2018)
This study aims to examine and analyze the effect of the influence of the work environment, organizational culture and motivation on employee performance at PT. Fast Food Indonesia, Tbk (KFC Indonesia). The data used in this study are primary data collected through questionnaires and other literature studies. The population in this study were employees of PT. Food Food Indonesia, Tbk. with a sample of 100 respondents. Data analysis techniques using path analysis with the help of SPSS 22 analysis system. Tests of data used in this study include validity test, reliability test, classical assumption test, sub structure I and Sub Structure 2 test, and path analysis (path analisys), to test and prove the research hypothesis.The results showed that the Work Environment and Organizational Culture had an effect on motivation. The work environment directly affects employee performance. Organizational Culture has a direct effect on Customer Employee Performance. Work Environment and Organizational Culture does not directly affect employee performance through motivation. Keywords: Work Environment, Organizational Culture, Motivation, Employee Performance